2015
DOI: 10.1111/are.12846
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two bacteriophages for specific treatment of biofilm formed by aVibriosp. isolated from an abalone farm

Abstract: Vibrio harveyi and related vibrios are potential pathogens causing luminous vibriosis in marine aquaculture systems. In this study, two lytic phages P4A and P4F isolated using Vibrio strains B4A and B4F as indicator bacteria, respectively, were isolated from seawater of an abalone farm. Vibrio strain B4F belongs to the Harveyi clade of the genus Vibrio and was found to cause mortality of abalones in laboratory microcosms. Both phages were able to lyse Vibrio strain B4F. Electron microscopy revealed that phage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Our results suggested that phages can be found in virtually all places where their related hosts exist. Several other investigations reported the presence of Vibrio-specific lytic phages in environmental water (shrimp ponds, aquaculture system, sea water and aquatic product market) from different regions of the world (Alagappan et al, 2010;Luo et al, 2016;Stalin and Srinivasan, 2016;Katharios et al, 2017;Srinivasan and Ramasamy, 2017;Yang M. et al, 2019).…”
Section: Origin and Morphology Of Phages Ba3 And Ca8mentioning
confidence: 99%
“…Our results suggested that phages can be found in virtually all places where their related hosts exist. Several other investigations reported the presence of Vibrio-specific lytic phages in environmental water (shrimp ponds, aquaculture system, sea water and aquatic product market) from different regions of the world (Alagappan et al, 2010;Luo et al, 2016;Stalin and Srinivasan, 2016;Katharios et al, 2017;Srinivasan and Ramasamy, 2017;Yang M. et al, 2019).…”
Section: Origin and Morphology Of Phages Ba3 And Ca8mentioning
confidence: 99%
“…The phage titre was determined by a drop count method (Luo et al, 2016). Ten-fold serial dilutions of the phage suspension was prepared in PBS buffer.…”
Section: Bacteriophage Identification Purification and Titrationmentioning
confidence: 99%
“…The results demonstrated that while phage treatment never fully prevented biofilm formation, biofilm biomass and cell density was significantly reduced ( Curtin and Donlan, 2006 ; Fu et al, 2010 ). Luo et al (2015) isolated two phages P4A and P4F which belong to the Siphoviridae family from seawater of an abalone farm and applied the phages to reduce Vibrio biofilm. In the study, the both phages were able to bring about 2 logs reduction in a Vibrio harveyi biofilm cell density after 24 h of phage treatment ( Luo et al, 2015 ).…”
Section: Advantages Of Phage Therapymentioning
confidence: 99%
“… Luo et al (2015) isolated two phages P4A and P4F which belong to the Siphoviridae family from seawater of an abalone farm and applied the phages to reduce Vibrio biofilm. In the study, the both phages were able to bring about 2 logs reduction in a Vibrio harveyi biofilm cell density after 24 h of phage treatment ( Luo et al, 2015 ).…”
Section: Advantages Of Phage Therapymentioning
confidence: 99%